Levan Produced by the Halophilic Bacterium Bacillus licheniformis BK1 as a Nanoparticle for Protein Immobilization - Ira Oktavia; Aidah Nur Fithriah; Nur Umriani Permatasari; Enny Ratnaningsih; Rukman Hertadi (Indonesian Journal of Chemistry, 2020)
This study examined the potential of levan from the halophilic bacterium Bacillus licheniformis BK1 as a nanoparticle system for protein immobilization. Levan produced by B. licheniformis BK1 was obtained by incubating the bacterium in the optimized Belghith medium, containing 15% (w/v) sucrose, 7.5% (w/v) NaCl and pH 8, in a rotary shaker at 150 rpm for 16 h, at 40 °C. The structure of the levan produced was verified by FTIR and NMR. It appeared that the levan had the same structure as that from Erwinia herbicola. The obtained levan was then used as a nanoparticle system to immobilize BSA and lysozyme proteins. The BSA-nanoparticle had a non-spherical shape with a surface charge of about -4.72 mV and a size distribution in the range of 83–298 nm. In contrast, the lysozyme-nanoparticle exhibited more spherical shapes with a surface charge of -2.57 mV and 206–285 nm size distribution. The efficiency of immobilization was about 74.26% and 81.77% for BSA and lysozyme, respectively. The study thus shows that levan produced by B. licheniformis BK1 can be used as a nanoparticle system for protein immobilization.